Taenionema (Plecoptera: Taeniopterygidae), a stonefly genus new to the fauna of China - Chen, Zhi-Teng; Ye, Xiao-Han (Zootaxa, 2020)
The taeniopterygid genus Taenionema Banks, 1905 is reported from China for the first time. A newly discovered and probable new species of this genus, Taenionema sp., is described and illustrated based on larvae from Zhejiang Province of coastal southeastern China. The species is characterized by the male larva having a bilobed post-genital plate. Adults will be necessary for a future formal species description. This contribution represents the first larval description in the family Taeniopterygidae from China.